2012
DOI: 10.1016/j.apcata.2011.10.036
|View full text |Cite
|
Sign up to set email alerts
|

Direct synthesis of DME from syngas on hybrid CuZnAl/ZSM-5 catalysts: New insights into the role of zeolite acidity

Abstract: A commercial HZSM-5 zeolite (Si/Al=16) was submitted to mild acid treatment and we have found that different conclusions regarding the effect of zeolite acidity may be reached depending on the specific method used for preparing the hybrid catalysts when the overall STD process becomes controlled by the methanol synthesis rate on the Cubased catalyst (i.e. using hybrids with a CZA:zeolite mass ratio of 2:1, that is, with an "excess" of acid sites). Thus, for hybrids prepared by mixing the pre-pelletized compone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
77
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 137 publications
(89 citation statements)
references
References 39 publications
(64 reference statements)
8
77
1
1
Order By: Relevance
“…This is valid for both metallic catalysts and their physical mixtures with all the three solid acid catalysts under the applied operating conditions. This is in agreement with the experimental results showing that interactions between the two components of the catalyst requires a proximity [12] which is not met in the hybrids prepared by physically mixing the pre-pelletized components [8,9,13]. In the absence of poisons from the applied ultra-pure premixed synthesis gases, as well as the absence of iron and nickel carbonyl formation [28] within the tubings and the reactor (as confirmed by XPS analysis of the spent catalysts, not shown), and the lack of any meaningful differences among the stabilities of the CZA, alone and in the hybrid catalysts, sintering of copper crystallites is probably the main cause of the catalyst deactivation.…”
Section: Catalyst Deactivationsupporting
confidence: 82%
See 1 more Smart Citation
“…This is valid for both metallic catalysts and their physical mixtures with all the three solid acid catalysts under the applied operating conditions. This is in agreement with the experimental results showing that interactions between the two components of the catalyst requires a proximity [12] which is not met in the hybrids prepared by physically mixing the pre-pelletized components [8,9,13]. In the absence of poisons from the applied ultra-pure premixed synthesis gases, as well as the absence of iron and nickel carbonyl formation [28] within the tubings and the reactor (as confirmed by XPS analysis of the spent catalysts, not shown), and the lack of any meaningful differences among the stabilities of the CZA, alone and in the hybrid catalysts, sintering of copper crystallites is probably the main cause of the catalyst deactivation.…”
Section: Catalyst Deactivationsupporting
confidence: 82%
“…Peng et al attributed the catalyst deactivation during slurry-phase direct DME synthesis to a detrimental interaction between the methanol synthesis catalyst and γ-alumina and hypothesized the migration of Cu-and Zn-contating species onto the acid catalyst as the likely mechanism [12]. Such adverse interactions between the metallic and the acid functions of the hybrid catalysts require an intimate solid-state contact between the two components, and hence, are highly dependent on the preparation method of the hybrid [8,9,12,13]. There have been several efforts to minimize these detrimental interactions in the hybrid catalysts with a high degree of interdispersion between their two components [11,14].…”
Section: Ch 3 Oh(g)mentioning
confidence: 99%
“…The changes of mol% DME, mol% MeOH and selectivities of the main products as function of time are represented in Figure (6) and Figure (7), respectively. It is clear that DME and methanol follow the same trend, as shown in Figure ( 6). DME production and MeOH production at 260 °C decreased from 10.5 % to 8.8 % and from 0.68 % to 0.58 %, respectively, which means that the admixed catalyst deactivated and lost around 16.2 % of its initial activity in the case of DME and 14.7 % of its initial activity in case of methanol.…”
Section: Catalyst Stability On Streammentioning
confidence: 49%
“…Furthermore the fact that the relative rates of the main reactions change considerably with temperature suggests that this ratio is also strongly related to the operating conditions of the reactor. Recently, García-Trenco et al [6] studied the effect of the preparation method on the stability of the catalyst and they found that the catalyst prepared by mixing the pre-pelletized components showed high stability with no signs of deactivation over 50 h. under operation are discussed. Within this manuscript we will focus on using a moderate pressure i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation